Clinical Efficacy of Injectable Herbal Heat Inducer in Anoestrous Murrah Buffaloes - BISWAS, J; RAY, S K; GIRI, S C; GIRI, S C; MITRA, J (The Indian Journal of Animal Reproduction, 2023)
Comparative study was made on Murrah buffaloes with three treatment_ regimes (Group- l. mineralmixture with COFECU tablet daily, Group-2. injectable herbal heat inducer (5ml i/m), Group-3. mineralmixture, COFECU and injectable herbal heat inducer (a preparation of Indian herbs), Group 4. controlwithout any treatment) to find the efficacy of drugs to induce estrous in post partum anoestrous animals. Itwas observed that the highest percentage (62.5) of animals exhibited estrous in group 3 followed by group 2.(50 %) and group I. (12.5 %). None of the animals were found to be in estrous in control group. Analysis ofdifferent blood parameters showed significant difference (p< 0.05) for total protein, cholesterol, calcium,phosphorus and manganese where as it was highly significant {p< 0.01) for copper, zinc and iron betweenbefore and after treatment for group :3. No significant difference was observed in any of the blood parametersin control group except copper. Therefore, it may be concluded that induction of estrous in buffaloes may be hastened with oral provision of mineral mixtures along with the injectable herbal heat inducer.
Keywords: Anoestrus; Estrous induction; Herbal heat inducer; Post partum